The dynamic interplay between saline fluid flow and rock permeability in magmatic‐hydrothermal systems. Issue 1 (23rd September 2014) - Weis, P.
Abstract Magmatic‐hydrothermal ore deposits document the interplay between saline fluid flow and rock permeability. Numerical simulations of multiphase flow of variably miscible, compressible H2O–NaCl fluids in concert with a dynamic permeability model can reproduce characteristics of porphyry copper and epithermal gold systems. This dynamic permeability model uses values between 10−22 and 10−13 m2, incorporating depth‐dependent permeability profiles characteristic for tectonically active crust as well as pressure‐ and temperature‐dependent relationships describing hydraulic fracturing and the transition from brittle to ductile rock behavior. In response to focused expulsion of magmatic fluids from a crystallizing upper crustal magma chamber, the hydrothermal system self‐organizes into a hydrological divide, separating an inner part dominated by ascending magmatic fluids under near‐lithostatic pressures from a surrounding outer part dominated by convection of colder meteoric fluids under near‐hydrostatic pressures. This hydrological divide also provides a mechanism to transport magmatic salt through the crust. With a volcano at the surface above the hydrothermal system, topography‐driven flow reverses the direction of the meteoric convection as compared to a flat surface, leading to discharge at distances of up to 7 km from the volcanic center. The same physical processes at similar permeability ranges, crustal depths, and flow rates are relevant for a number of active systems, including geothermal resources and excess degassing at volcanos. The simulations further suggest that the described mechanism can separate the base of free convection in high‐enthalpy geothermal systems from the magma chamber as a driving heat source by several kilometers in the vertical direction in tectonic settings with hydrous magmatism. These root zones of high‐enthalpy systems may serve as so‐called super‐critical geothermal resources. This hydrology would be in contrast to settings with anhydrous magmatism, where the base of the geothermal systems may be closer to the magma chamber.